High-energy signatures of binary supermassive black holes - Vila, Gabriela Soledad (2013)
Some active galactic nuclei are supposed to harbor binary systems of supermassive black holes. They are an attractive target for gravitational wave experiments. The identification of these systems is mostly based on the detection of periodic features in their light curves. Such identifications, however, are far from being conclusive. In this work we study the perturbations in the emission spectrum of the accretion disk of the primary black hole caused by the orbital motion of the secondary. Then we proceed to determine the kind of spectral energy distributions expected at gamma-ray energies from the inverse Compton up-scattering of disk photons by relativistic electrons in a jet. Gamma-ray observations with instruments such as the future Cherenkov Telescope Array may contribute to a definitive identification of supermassive binary black hole systems at high-energies.